Old Yeller. - Gipson, Fred, 1908-; Burger, Carl - illus (New York : Harper, 1956)
In the late 1860s in the Texas hill country, a big yellow dog and a fourteen-year-old boy form a close, loving relationship.
Keywords: Dogs -- Fiction; Frontier and pioneer life -- Fiction; Newbery honor book